Bioinspired 4D Transdermal Microneedles for the advanced drug delivery: Current status and future prospects - Razzak, Adiba Binte (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2021.